Impact of Sulphur Content on Coal Quality at Delta Plain Depositional Environment: Case study in Geramat District, Lahat Regency, South Sumatra - Sari, Siska Linda; Rahmawati, Mutia Armilia; Triyoga, Alan; Wati, Idar (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
The research was conducted in Geramat District of Lahat Regency, South Sumatra. An evaluation of the geological condition of the research area shown that the coal deposits were found in Muara Enim Formation as a coal-bearing formation. The method used was literature study, field observation and the laboratory work includes proximate and petrography analysis. The aim of this research is to determine the environmental condition of coal based on the change of total sulphur content and to know the relation between ash content to calorific value.  As the result of proximate analysis conducted on five samples of coal, the research area obtained total sulphur (0,21-1,54% adb), ash content (3,16 - 71,11% adb) and gross calorific value (953 - 5676 cal/g. adb). Based on the result of maceral analysis showed the maceral percentage of coal in research area composed by vitrinite (77,8-87,4 %), liptinite (0,6 %), inertinite (8,0 – 17,6 %) and mineral matter concentration in the form of pyrite (1,6-4,6 %). The average reflectance value of vitrinite (Rv) of coal in the research area (0.54%). the results analysis shows that the coal in Muara Enim Formation on the research area is in the transitional lower delta plain depositional environment phase. Any changes in the sedimentary environment affected by sea water will be followed by changes in total sulphur and the higher ash content, on the contrary, the lower calorific value of the coal.